2017
DOI: 10.1073/pnas.1706656114
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal signaling of the receptor for calcitonin gene-related peptide mediates pain transmission

Abstract: G protein-coupled receptors (GPCRs) are considered to function primarily at the plasma membrane, where they interact with extracellular ligands and couple to G proteins that transmit intracellular signals. Consequently, therapeutic drugs are designed to target GPCRs at the plasma membrane. Activated GPCRs undergo clathrin-dependent endocytosis. Whether GPCRs in endosomes control pathophysiological processes in vivo and are therapeutic targets remains uncertain. We investigated the contribution of endosomal sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
179
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(188 citation statements)
references
References 29 publications
9
179
0
Order By: Relevance
“…Another is to deliberately exploit the potential of conformationally selective nanobodies to block GPCR signaling reactions, specifically localizing them to a defined target membrane using chemical recruitment tools and assessing effect on the cellular response . A third approach, which may also have therapeutic potential with further development, is to generate antagonist ligands that accumulate in endosomes to inhibit activation in this compartment selectively …”
Section: G Protein Signaling From Endosomes: a Continuation Or New Bementioning
confidence: 99%
See 2 more Smart Citations
“…Another is to deliberately exploit the potential of conformationally selective nanobodies to block GPCR signaling reactions, specifically localizing them to a defined target membrane using chemical recruitment tools and assessing effect on the cellular response . A third approach, which may also have therapeutic potential with further development, is to generate antagonist ligands that accumulate in endosomes to inhibit activation in this compartment selectively …”
Section: G Protein Signaling From Endosomes: a Continuation Or New Bementioning
confidence: 99%
“…13,37 Over the last decade, however, the hypothesis that GPCRs can initiate G protein-coupled signaling from endosomes as well as the plasma membrane has gained considerable experimental support. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Evidence for GPCR-G protein signaling from endosomes. Broadly considered, four experimental approaches have produced evidence supporting endosomal GPCR-G protein signaling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed the importance of the texture of the initiated intracellular signal in controlling unique physiological outcomes, including both spatial (i.e., subcellular compartmentalisation of the signal) and temporal (i.e., changes in the signal over time) properties (Calebiro et al, ; DeFea, ; Godbole, Lyga, Lohse, & Calebiro, ; Irannejad et al, ; Irannejad et al, ; Kotowski, Hopf, Seif, Bonci, & von Zastrow, ; Mullershausen et al, ; Nikolaev, Bünemann, Schmitteckert, Lohse, & Engelhardt, ; Tsvetanova & von Zastrow, ; Wehbi et al, ). These shifts in the way we understand canonical GPCR activation and downstream signalling are already opening exciting new avenues for drug discovery (Jensen et al, ; Jimenez‐Vargas et al, ; Yarwood et al, ).…”
Section: G‐protein Coupled Receptorsmentioning
confidence: 99%
“…Recent advances in the understanding of compartmentalised GPCR signalling have illustrated the importance of receptor location (within different plasma membrane domains or within different subcellular compartments) for the control of distinct signalling outcomes (Halls et al, 2016;Jensen et al, 2017;Jimenez-Vargas et al, 2018;Stoeber et al, 2018;Tsvetanova & von Zastrow, 2014;Yarwood et al, 2017). Cellular context also appears to be very important in order for GPCRs to respond to ultra-low concentrations of ligand ( Figure 1).…”
Section: Other Gpcrs Can Generate Ultra-sensitive Cellular Responsesmentioning
confidence: 99%